Pulmonary endarterectomy in the management of chronic thromboembolic pulmonary hypertension. (15th March 2017) - Jenkins, David; Madani, Michael; Fadel, Elie; D'Armini, Andrea Maria; Mayer, Eckhard
Chronic thromboembolic pulmonary hypertension (CTEPH) is a type of pulmonary hypertension, resulting from fibrotic transformation of pulmonary artery clots causing chronic obstruction in macroscopic pulmonary arteries and associated vascular remodelling in the microvasculature. Pulmonary endarterectomy (PEA) offers the best chance of symptomatic and prognostic improvement in eligible patients; in expert centres, it has excellent results. Current in-hospital mortality rates are <5% and survival is >90% at 1 year and >70% at 10 years. However, PEA, is a complex procedure and relies on a multidisciplinary CTEPH team led by an experienced surgeon to decide on an individual's operability, which is determined primarily by lesion location and the haemodynamic parameters. Therefore, treatment of patients with CTEPH depends largely on subjective judgements of eligibility for surgery by the CTEPH team. Other controversies discussed in this article include eligibility for PEA versus balloon pulmonary angioplasty, the new treatment algorithm in the European Society of Cardiology/European Respiratory Society guidelines and the definition of an "expert centre" for the management of this condition. Pulmonary endarterectomy in an expert centre is the treatment of choice for eligible patients with CTEPH http://ow.ly/T0kv308BGeY